In Situ SERS Monitoring the Visible Light Photocatalytic Degradation of Nile Blue on Ag@AgCl Single Hollow Cube as a Microreactor. Issue 2 (9th January 2018) - Li, Dingyi; Ouyang, Lei; Yao, Ling; Zhu, Lihua; Jiang, Xiaoqing; Tang, Heqing
Abstract: Reaction monitoring and mechanism study for catalytic processes are important for catalyst design and application, and surface enhanced Raman scattering (SERS) is a promising tool in this area because of its high sensitivity and non‐destructive detection mode. Here a new strategy was proposed for fabricating a micro‐scale Ag@AgCl hollow cube as both a uniform and active photocatalyst and a SERS sensing framework. It was confirmed that the stable micro cube was able to be used as a single particle based platform for SERS monitoring of the photocatalytic reaction on it. This bifunctional material hold both strong SERS enhancement ability (enhancement factor up to 2.4×10 8 ) and high photocatalytic activity. Such a micro‐reactor was successfully applied to in situ track the photocatalytic degradation reaction of Nile blue (NB). The SERS monitoring data showed that this photocatalytic reaction apparently followed a pseudo‐first‐order reaction model in kinetics with a rate constant of 0.557 min −1 . By looking into the molecular finger‐print information acquired from SERS monitoring, the pathways of the photocatalytic degradation of NB were clarified, which involved the cleavages of two backbones in NB hetero‐ring and the direct oxidation cleavage of naphthalene, as supported by the liquid chromatograph‐mass spectroscopic analysis of the degradation intermediates. Abstract : A bifunctional Ag@AgCl hollow cubes were fabricated as both photocatalyst and SERS monitoring substrate. On such single particle based platform, the kinetics for visible light photocatalytic degradation of Nile blue were in situ monitored by SERS with insight into its molecular mechanism.